2022
DOI: 10.1016/j.xjidi.2021.100070
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreens with the New MCE Filter Cover the Whole UV Spectrum: Improved UVA1 Photoprotection In Vitro and in a Randomized Controlled Trial

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…By calculating the ΔΔE, between reference + MCE and reference the difference of pigmentation between both sunscreen formulations starts at 24 h after the first exposure (1. 38 The visual assessment confirmed colorimetric data and showed a lower pigmentation level for reference + MCE versus reference (Figure 4). This difference was about one point at each time point with p < 0.001 starting 24 h after the first exposure.…”
Section: Study 2 (Duvr Spectrum)supporting
confidence: 62%
See 3 more Smart Citations
“…By calculating the ΔΔE, between reference + MCE and reference the difference of pigmentation between both sunscreen formulations starts at 24 h after the first exposure (1. 38 The visual assessment confirmed colorimetric data and showed a lower pigmentation level for reference + MCE versus reference (Figure 4). This difference was about one point at each time point with p < 0.001 starting 24 h after the first exposure.…”
Section: Study 2 (Duvr Spectrum)supporting
confidence: 62%
“…As a result, MCE broadens the level of absorption provided in the UVA1 range. It has been shown that the addition of this filter in a reference sunscreen formulation (at the same SPF value and a similar profile of absorption up to ∼360–370 nm) can prevent biological alterations 38 . In vitro, using a three‐dimensional skin model, epidermal and dermal alterations induced by UVA1 exposure as well as in vivo induced pigmentation were significantly reduced using formulations containing MCE at 0.7% or 1.5% compared to a sunscreen formulation lacking absorption in the 370–400 nm wavelength range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is today listed in Annex VI of the EU-authorized UV filters. In a very recent paper, it was shown that the addition of MCE in reference formulas enlarged the profile of absorption up to 400 nm, leading to the coverage of the full UV spectrum, and improved UVA1 photoprotection by reducing UVA1-induced dermal and epidermal alterations at the cellular, biochemical and molecular levels as well as decreasing UVA1-induced pigmentation [ 264 ]. These data under controlled UVA1 exposures have been confirmed under a full UV (UVB and UVA) spectrum up to real sun exposure, supporting the benefit of full UVB and UVA profiles of absorption in natural sunlight exposures [ 265 ].…”
Section: Rationale For a Broadened Photoprotection Including Uva1mentioning
confidence: 99%